Neural mechanism of HT7 electroacupuncture in myocardial ischemia: critical role of the paraventricular nucleus oxytocin system - Wu, Hao-Sheng; Zhu, Li; Liu, Pan; Liu, Xiao-Hui; Su, Hang; Zheng, Xin-Yi; Liu, Tong-Tong; Cui, Shuai; Wu, Sheng-Bin; Zhou, Mei-Qi; Zhu, Chao (Frontiers in Neuroscience, 2025)
ObjectiveElectroacupuncture (EA) at Shenmen (HT7) alleviates acute myocardial ischemia (AMI), but its central neuromodulatory mechanisms remain insufficiently defined. This study investigated whether oxytocinergic (OT) neurons in the hypothalamic paraventricular nucleus (PVN) mediate the cardioprotective effects of EA and verified causality through chemogenetic interventions.MethodsPart I: C57BL/6 mice (n = 18) were allocated into three groups: sham, AMI, and AMI + EA-HT7 (2 Hz/1 mA, 30 min/day × 3 days). Cardiac function (echocardiography), histopathology (HE/Masson staining), and PVN electrophysiology were evaluated. Part II: C57BL/6 mice (n = 18) were divided into sham, AMI, and AMI + EA-HT7 groups. Mice received AAV-hSyn-DIO-mCherry and AAV-cre-OT injections into the PVN. EA-induced neuronal activation was quantified by c-Fos and OT co-localization. Part III: C57BL/6 mice (n = 18) were assigned to chemogenetic activation (OT-activation), inhibition (OT-inhibition), and control (OT-control) groups. Under physiological conditions, the effects of chemogenetic modulation on PVN electrophysiology, electrocardiography, and echocardiography were assessed. Part IV: C57BL/6 mice (n = 24) were divided into AMI + OT-control, AMI + EA-HT7 + OT-control, AMI + OT-inhibition, and AMI + EA-HT7 + OT-activation groups. Under pathological conditions, the effects of chemogenetic regulation on PVN physiology and cardiac function were examined.ResultsEA at HT7 improved left ventricular ejection fraction (p < 0.05), correlating with suppression of PVN neuronal firing. EA specifically inhibited PVNOT neuronal activity (p < 0.05). Under physiological conditions, chemogenetic modulation of PVNOT neurons altered local electrophysiological activity and cardiac performance. In AMI mice, OT neuronal activation reversed EA-induced cardioprotection (p < 0.05).ConclusionPVN oxytocinergic neurons are both necessary and sufficient for the cardioprotective effects of EA at HT7. Chemogenetic regulation confirms a causal neurocardiac axis, providing mechanistic insights that support precision acupuncture therapies for ischemic heart disease.